Virtual Literatures: Technology, Agency, Meaning. Issue 3 (December 2016) - Carter, Richard
Abstract : What does it mean when the technologies and techniques of literary expression intersect with those of simulated virtual environments? Specifically, how are the expressive properties of scriptural markings reshaped and recast when conveyed and received through modes of viewing and interaction afforded by digital rather than printed spaces? Virtual-literary works such as New Word Order: Basra (2003) and Dear Esther (2012) raise just these questions, which have significant implications for conceptualising the literary experience within a digital context. This article develops a response to these issues by concentrating less on the technical differences between printed and digital media and focusing instead on how their expressive potential is actualised within the space of the interpretative encounter. It presents a model, derived from work in the sociology of science and the digital humanities, in which the literary is understood as emerging from a performative matrix of intersecting actors, materials, and processes in real time – of which the medium is one component. From this standpoint, the significance of the virtual-literary encounter is that it represents an extension of these performative vectors into comparatively novel digital contexts, enabling different narrative, thematic, and semantic aspects to be crystallised in relation to alternative technocultural developments. Such encounters are countertextual in demonstrating the potentialities of literary expression beyond the naturalised spaces of print – a reframing rather than a superseding of the literary.